ปริมาณสารต้านอนุมูลอิสระและการตรวจสอบคุณภาพทางจุลชีววิทยาในน้ำจากลำไผ่พันธุ์นวลราชินี (Dendrocalamus sericeus Munro) และกิมซุง (Bambusa beecheyana) - หาระโคตร พรชัย; พวงจิก ธัญพิสิษฐ์; ทะบันหาร สมพงษ์ (Thai Journal of Science and Technology, 2019)
Abstract This study aimed to determine total phenolic content, total flavonoid content, antioxidant capacities and microbial qualities of raw bamboo water, boiled bamboo water, and pasteurized bamboo water, which were obtained from Nual Rachinee (Dendrocalamus sericeus Munro) and Kim Chung (Bambusa beecheyana) bamboo. The results indicated that Kim Chung bamboo water gave the total phenolic content and antioxidant capacities higher than those of Nual Rachinee bamboo water. Heat treatment methods have been shown to increase bioactive compounds in bamboo water. The boiled Nual Rachinee bamboo water had the highest levels of total phenolics and flavonoids. However, there were low concentrations of antioxidant compounds and their capacities as compared with vitamin C. Studies on microbial quality found mold contamination in raw Nual Rachinee bamboo water as well as yeast contamination in raw Kim Chung bamboo water. Therefore, raw bamboo water cannot be directly consumed as healthy drinking water. Keywords: bamboo; bamboo water; antioxidant; microbial contamination